Transition properties of five lowest–lying singlet and three lowest–lying triplet states of silicon monosulphide molecule. (September 2021) - Zhang, Jinping; Li, Hui; Ma, Yanqin
Highlights: b 3 Π – d 3 Δ transition is weak. A 1 Π – X 1 Σ + and E 1 Σ + – X 1 Σ + transitions are strong. Lifetime is 4.3 – 9.8 ms for the a 3 Σ + 1 state and 3.8 – 35.4 ms for a 3 Σ + 0– state. Lifetime is 117 – 380 μs for the b 3 Π0+ state and 73 – 581 μs for the b 3 Π1 state. Lifetime is 107.6 – 120.5 ns for the A 1 Π state and 12.8 – 14.1 ns for the E 1 Σ + state. Abstract: The transition properties of the X 1 Σ +, C 1 Σ –, D 1 Δ, A 1 Π, E 1 Σ +, a 3 Σ +, d 3 Δ, and b 3 Π states of silicon monosulphide were investigated using the complete active space self-consistent field method, which was followed by the internally contracted multireference configuration interaction approach. The transition dipole moments were calculated for the dipole–allowed transitions between these singlet states and for all transitions between the X 1 Σ +, a 3 Σ +, d 3 Δ, and b 3 Π states. The radiative lifetimes of the first 16 vibrational levels were 107.6 – 120.5 ns for the A 1 Π state and 12.8 – 14.1 ns for the E 1 Σ + state. Among these dipole–allowed transitions, the emissions from the A 1 Π – X 1 Σ + and E 1 Σ + – X 1 Σ + systems were strong, whereas those from the b 3 Π – d 3 Δ system were weak. The radiative lifetimes of the first 16 levels were 4.3 – 9.8, 3.8 – 35.4, 2.2 – 7.9, and 11.9 – 14.5 ms for the a 3 Σ + 1, a 3 Σ + 0–, d 3 Δ1, and d 3 Δ2 states, respectively. These were 117 – 380, 73 – 581, and 137 – 586 μs for the b 3 Π0+, b 3 Π1, and b 3 Π2 states, respectively. Among these forbidden transitions, the b 3 Π0+ – X 1 Σ + 0+ and b 3 Π1 – X 1 Σ + 0+ transitions were the strongest. The Franck–Condon factors, Einstein A coefficients, and band origins of all these spontaneous emissions were calculated. The transition properties were compared with the available experimental and theoretical results. Graphical abstract: The transition properties of the X 1 Σ +, C 1 Σ –, D 1 Δ, A 1 Π, E 1 Σ +, a 3 Σ +, d 3 Δ, and b 3 Π states of SiS are calculated; the TDMs of the dipole–allowed transitions between the singlet states are determined; and the TDMs of all transitions between the X 1 Σ +, a 3 Σ +, d 3 Δ, and b 3 Π states are computed. The radiative lifetimes of the first 16 vibrational levels are 107.6 – 120.5 ns for the A 1 Π state and 12.8 – 14.1 ns for the E 1 Σ + state. These are 4.3 – 9.8, 3.8 – 35.4, 2.2 – 7.9, and 11.9 – 14.5 ms for the a 3 Σ + 1, a 3 Σ + 0–, d 3 Δ1, and d 3 Δ2 states, respectively. And these are 117 – 380, 73 – 581, and 137 – 586 μs for the b 3 Π0+, b 3 Π1, and b 3 Π2 states, respectively. Among all dipole–allowed transitions, the A 1 Π – X 1 Σ + and E 1 Σ + – X 1 Σ + transitions are strong, whereas the b 3 Π – d 3 Δ transition is weak. Among all forbidden transitions, the b 3 Π0+ – X 1 Σ + 0+ and b 3 Π1 – X 1 Σ + 0+ transitions are the strongest. Image, graphical abstract